Twin Peaks como alegoria daimónica cinematográfica - Chinita, Fátima (2014)
For a long time the allegorical activity was considered dogmatic and equated with artistic fossilization, archaic religious propensity and lack of creativity. However, Walter Benjamin (1928) and Paul De Man (1969), among other illustrious thinkers, came to its defense, exalting, instead, its cryptic, hybrid and abstract nature, which, incidentally, are the main characteristics of modern art. “Twin Peaks – Fire Walk with Me” (David Lynch, 1992) is a wonderful object of analysis, despite being one of the most misunderstood films in the history of cinema. The fact that its narrative is a prequel to the cult television series “Twin Peaks” and incorporates many of the characters of that show, explicitly denigrating the moral image of the protagonist, Laura Palmer, brought about an intense rejection by the fans of the series, as well as the indifference of the cinephilic community in general. However, one must go deeper, in order to understand Lynch’s brave accomplishment and its artfulness. Indeed, the opus is a powerful cinematic allegory because it contains a double layer of metaphorical meaning, one of them being explicitly metacinematic. Thus, besides assuming itself as a filmic daimonic allegory, occurring in a spiritual universe of Good versus Evil, the film is also an authorial discourse on cinema itself. More specifically, it is an allegory of spectatorship, according to Robert Stam’s definition, where the existence and crossing over to “another side” duplicates the architecture of movie theatres and the psychic processes involved in film viewing.